Assessing the national health information system : an assessment tool (World Health Organization, 2008)
This Health Metrics Network assessment tool is intended to achieve more than a assessment of the strengths and weaknesses of the elements and operations of a national HIS. The mere process of conducting the assessment reaches and engages all stakeholders in the system. In order to assist countries in this key activity Health Metrics Network has developed this assessment tool which describes in detail how to undertake a first baseline assessment.
Health metrics network
Keywords: informační systémy; Information Systems; Medical Informatics Applications; Data Collection; sběr dat; lékařská informatika; management, organizace a řízení zdravotnictví; zdravotnické plánování - podpora; využití lékařské informatiky; systémy podporující rozhodování v léčbě; Medical Order Entry Systems; Health Planning Support